PERAN KUALITAS PRODUK DAN KUALITAS LAYANAN DALAM MENINGKATKAN KEPUASAN KONSUMEN (STUDI KASUS INFORMA CABANG MAL ARTHA GADING) - Napitululu, Arie Martin Parulian; Zico, Ardiles; Napitupulu, Rina Dameria (Jurnal Manajemen & Bisnis Jayakarta, 2024)
This research aims to analyze the role of product quality and service quality in increasing consumer satisfaction at Informa Artha Gading Mal Branch, as well as to analyze the supporting and inhibiting factors for the role of product quality and service quality in increasing consumer satisfaction at Informa Artha Gading Mal Branch. The type of research used is descriptive qualitative research with data collection techniques in the form of interviews, observation and documentation. The data analysis technique was carried out based on the Miles & Huberman concept, namely data collection, data reduction, data presentation and drawing conclusions. The research results show that product quality at Informa Artha Gading Mal Branch, in this case, plays a role in providing guarantees that the company has superior products compared to its competitors so that consumers feel satisfied. Meanwhile, the quality of service at Informa Mal Artha Gading Branch plays a role in creating a good shopping experience so that it can increase consumer satisfaction. Supporting factors for the role of product quality and service quality in increasing consumer satisfaction at Informa Mal Artha Gading Branch are the good skills of employees and the existence of a positive work environment. Meanwhile, the inhibiting factor in the role of product quality and service quality in increasing consumer satisfaction at Informa Artha Gading Mal Branch is the company's inability to predict the number of consumers per day.